Cancer Immunotherapy Using CAR‐T Cells: From the Research Bench to the Assembly Line. Issue 2 (30th October 2017) - Gomes‐Silva, Diogo; Ramos, Carlos A.
Abstract : The focus of cancer treatment has recently shifted toward targeted therapies, including immunotherapy, which allow better individualization of care and are hoped to increase the probability of success for patients. Specifically, T cells genetically modified to express chimeric antigen receptors (CARs; CAR‐T cells) have generated exciting results. Recent clinical successes with this cutting‐edge therapy have helped to push CAR‐T cells toward approval for wider use. However, several limitations need to be addressed before the widespread use of CAR‐T cells as a standard treatment. Here, a succinct background on adoptive T‐cell therapy (ATCT)is given. A brief overview of the structure of CARs, how they are introduced into T cells, and how CAR‐T cell expansion and selection is achieved in vitro is then presented. Some of the challenges in CAR design are discussed, as well as the difficulties that arise in large‐scale CAR‐T cell manufacture that will need to be addressed to achieve successful commercialization of this type of cell therapy. Finally, developments already on the horizon are discussed. Abstract : A chimeric antigen receptor (CAR), which fuses an antibody‐derived antigen recognition domain with T‐cell activating domains, can be genetically introduced into T cells to allow them to directly bind and kill tumor cells that display that antigen. Clinical application of CAR‐expressing T cells (CAR‐T cells) has met significant success in B‐cell malignancies. Current methods of CAR‐T cell manufacture and challenges in the commercialization of this type of cell therapy are reviewed.